Decoration of silver nanoparticles on nitrogen-doped nanoporous carbon derived from zeolitic imidazole framework-8 (ZIF-8) via in situ auto-reduction. Issue 12 (9th February 2021) - Veeramani, Vediyappan; Van Chi, Nguyen; Yang, Yi-Lin; Hong Huong, Nguyen Thi; Van Tran, Thuan; Ahamad, Tansir; Alshehri, Saad M.; Wu, Kevin C.-W.
Abstract : Unremoved metal residue and no utilization of reducing agent could be applied for synthesizing metal-supported catalyst. Abstract : We discovered an in situ auto-reduction method to embed silver nanoparticles onto a nanoporous carbon (NC) derived from the zeolitic imidazole framework-8 (ZIF-8), without any requirement of the reducing agents. The detailed analysis demonstrated the formation of Ag NPs by the replacement of the metallic Zn residue in the NC with Ag ions. The synthesized Ag@NC exhibited a superior catalytic activity toward the reduction reaction of 4-nitrophenol into 4-aminophenol.